Use of the CR100 scale for session rating of perceived exertion in soccer and its interchangeability with the CR10 - Fanchini, M.; Ferraresi, I.; Modena, R.; Schena, F.; Coutts, A. J.; Impellizzeri, F. M. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To examine the construct validity of the session rating perceived exertion (s-RPE) assessed with the Borg CR100 scale to measure training loads in elite soccer and to examine if the CR100 is interchangeable and can provide more-accurate ratings than the CR10 scale.